Spectral signatures of serotonergic psychedelics and glutamatergic dissociatives - Pallavicini, Carla (2019)
Classic serotonergic psychedelics are remarkable for their capacity to induce reversible alterations in consciousness of the self and the surroundings, mediated by agonism at serotonin 5-HT2A receptors. The subjective effects elicited by dissociative drugs acting as N-methyl-D-aspartate (NMDA) antagonists (e.g. ketamine and phencyclidine) overlap in certain domains with those of serotonergic psychedelics, suggesting some potential similarities in the brain activity patterns induced by both classes of drugs, despite different pharmacological mechanisms of action. We investigated source-localized magnetoencephalography recordings to determine the frequency-specific changes in oscillatory activity and long-range functional coupling that are common to two serotonergic compounds (lysergic acid diethylamide [LSD] and psilocybin) and the NMDA-antagonist ketamine. Administration of the three drugs resulted in widespread and broadband spectral power reductions. We established their similarity by using different pairs of compounds to train and subsequently evaluate multivariate machine learning classifiers. After applying the same methodology to functional connectivity values, we observed a pattern of occipital, parietal and frontal decreases in the low alpha and theta bands that were specific to LSD and psilocybin, as well as decreases in the low beta band common to the three drugs. Our results represent a first effort in the direction of quantifying the similarity of large-scale brain activity patterns induced by drugs of different mechanism of action, confirming the link between changes in theta and alpha oscillations and 5-HT2A agonism, while also revealing the decoupling of activity in the beta band as an effect shared between NMDA antagonists and 5-HT2A agonists. We discuss how these frequency-specific convergences and divergences in the power and functional connectivity of brain oscillations might relate to the overlapping subjective effects of serotonergic psychedelics and glutamatergic dissociative compounds.